2019
DOI: 10.1111/psyp.13321
|View full text |Cite
|
Sign up to set email alerts
|

Do emojis influence social interactions? Neural and behavioral responses to affective emojis in bargaining situations

Abstract: Emojis are nowadays a common substitute for real facial expressions to integrate emotions in social interaction. In certain contexts, emojis possibly could also transport information beyond emotions, reflecting interindividual differences or social aspects. In this study, we investigated the influence of emojis as socioemotional feedback stimuli on behavior and neural responses in a social decision game. We modified the Ultimatum Game by including emotional feedback provided by the proposer as response to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 73 publications
1
13
0
Order By: Relevance
“…Noisy channels (2 channels across all participants) were substituted using interpolation according to a visual inspection of the variance across time pointes. For artifact rejection, trials in which the amplitude exceeded the criterion of absolute amplitude of 300 μV within a segment or the joint probability of 4 standard deviations (joint probability of an electrode’s activity in a segment given that same electrode’s activity in all other segments or joint probability of an electrode’s activity in a segment given all other electrodes’ activities for that same segment) were excluded from further analyses (7.5% of the trials) 39 . At least 10 artifact-free trials were available per participant and condition (M = 16.6).…”
Section: Methodsmentioning
confidence: 99%
“…Noisy channels (2 channels across all participants) were substituted using interpolation according to a visual inspection of the variance across time pointes. For artifact rejection, trials in which the amplitude exceeded the criterion of absolute amplitude of 300 μV within a segment or the joint probability of 4 standard deviations (joint probability of an electrode’s activity in a segment given that same electrode’s activity in all other segments or joint probability of an electrode’s activity in a segment given all other electrodes’ activities for that same segment) were excluded from further analyses (7.5% of the trials) 39 . At least 10 artifact-free trials were available per participant and condition (M = 16.6).…”
Section: Methodsmentioning
confidence: 99%
“…It was concluded that 36 out of 91 emojis were significantly associated with extraversion, emotional stability and agreeableness. Other studies have been conducted regarding the use of emojis, especially in psychology [20][21][22][23]; yet there is only limited data on the effects of these pictographs in other fields of medicine. The latter is mainly due to the availability of many emojis describing emotion and behavior, while only a few emojis are precisely related to health and medical terms.…”
Section: Emojis In Healthcare Literaturementioning
confidence: 99%
“…Afterward, we applied the extensions ADJUST (Mognon, Jovicich, Bruzzone, & Buiatti, 2011) and MARA (Winkler, Haufe, & Tangermann, 2011), which operate with SASICA software (Chaumon, Bishop, & Busch, 2015) to choose ICA components for artifact rejection. Offline reference was transformed to current source density like in other ERP studies before (Kayser et al, 2010;Milne, 2011;Weiß et al, 2019a), and data were filtered with a 20-Hz low pass filter. Statistical calculations were conducted for each participant for each condition ±20 ms around the positive or negative peak, respectively.…”
Section: Eeg Recording and Quantificationmentioning
confidence: 99%
“…Statistical calculations were conducted for each participant for each condition ±20 ms around the positive or negative peak, respectively. N170 latency was quantified as the negative peak between 130 and 210 ms (Johnston, Molyneux, & Young, 2014;Mussel et al, 2018;Weiß et al, 2019a) pooled at electrodes P7 and P8. Latencies for FRN were calculated as the negative peak between 200 and 400 ms at electrode site FCz,…”
Section: Eeg Recording and Quantificationmentioning
confidence: 99%
See 1 more Smart Citation